The Effectiveness of Legal Protection and Strategies to Minimize Domestic Violence against the Elderly - Martha, Aroma Elmina; Ali, Mahrus (Technium Social Sciences Journal, 2023)
Few studies have examined the annually increasing cases of violence against the elderly in Indonesia. This study aimed to analyze the effectiveness of protection and propose a theoretical strategy to minimize violence against the elderly. It used a normative approach to examine Law Number 23 of 2004 concerning the Elimination of Domestic Violence and Law Number 13 of 2008 on the Elderly Welfare as protection indicators. The findings showed that the elderly needed preventive and repressive legal protection. This means it is important to protect the elderly against violence by resecting them regardless of gender. Therefore, efforts should be made to protect the elderly from neglect as part of domestic violence by changing laws and regulations related to the substance and mechanisms for legal protection.